2021
DOI: 10.3390/cancers13174305
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Small Intestinal Neuroendocrine Tumours Contains Lymphocytes Capable of Recognition and Activation after Expansion

Abstract: Traditionally, immune evasion and immunotherapy have been studied in cancers with a high mutational load such as melanoma or lung cancer. In contrast, small intestinal neuroendocrine tumours (SINETs) present a low frequency of somatic mutations and are described as genetically stable tumours, rendering immunotherapies largely unchartered waters for SINET patients. SINETs frequently metastasise to the regional lymph nodes and liver at the time of diagnosis, and no curative treatments are currently available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…IHC staining for the proliferation marker, Ki67 showed similar numbers of Ki67+ cells per field of view in NEN PDTOs and their matched parental tumors (Figure 2C and S2C). In line with these data, a comparison of the mRNA expression of MKI67 in PDTOs derived from tumors of different grades confirmed that all PDTOs presented MKI67 expression levels within what has been reported in their respective histopathological type (Alcala et al, 2019;Alvarez et al, 2018;Hofving et al, 2021) (Figure 2D).…”
Section: Nen Pdtos Recapitulate Disease-specific Growth Phenotypessupporting
confidence: 88%
“…IHC staining for the proliferation marker, Ki67 showed similar numbers of Ki67+ cells per field of view in NEN PDTOs and their matched parental tumors (Figure 2C and S2C). In line with these data, a comparison of the mRNA expression of MKI67 in PDTOs derived from tumors of different grades confirmed that all PDTOs presented MKI67 expression levels within what has been reported in their respective histopathological type (Alcala et al, 2019;Alvarez et al, 2018;Hofving et al, 2021) (Figure 2D).…”
Section: Nen Pdtos Recapitulate Disease-specific Growth Phenotypessupporting
confidence: 88%
“…Cell suspensions were stained, as described [37,40]. Briefly, cell viability in 1 mL cell suspension containing 1 million cells was determined by Zombie Red Fixable viability dye (Biolegend), followed by 20 min incubation with fluorescence-conjugated antibodies (Supplementary Table S2).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…We expanded TILs in vitro from the CRLM from two patients ( Figure 3 A–E) for subsequent transfer to lymphocyte-deficient PDX mice bearing subcutaneous tumor implants derived from the autologous CRLM, as previously described [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cell suspensions were stained as previously described [ 13 , 24 , 27 ]. Briefly, cell viability was determined by Zombie Red Fixable viability dye (Biolegend, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation